Japan's shifting security posture in Southeast Asia - Panut, Yopi Irianto (2024)
In recent months, Japan launched a new security initiative aimed at strengthening its relations with countries in Southeast Asia and bolstering their military capabilities. This shift in its security posture is driven by the need to counter the rise of China. Japan’s move will likely find support among most of the ASEAN Member States given the salutory effect on regional stability.